Environmental markets : equity and efficiency - Chichilnisky, Graciela; Heal, G. M. (Economics for a sustainable earth series., 2000)
Markets are increasingly central to the resolution of environmental problems. They played a critical role in implementing the 1990 Clean Air Act of the United States, which has been instrumental in reducing acid rain in a cost-effective manner. They are also central to the global strategy adopted for limiting the emissions of greenhouse gases under the 1997 Kyoto Protocol and are being used for resolving conflicts over the use of other environmental resources, particularly water. Environmental Markets: Equity and Efficiency represents the first systematic and in-depth study of the economic issues raised by this growing use of environmental markets. Focusing on the relationship between equity and efficiency -- which is central to many of the debates between industrial and developing countries -- the book explores the underlying economics and the possibilities for win-win solutions that benefit all parties to the problems. Graciela Chichilnisky and Geoffrey Heal have been instrumental in developing the economic understanding required for the operation of environmental markets and for promoting their use among policy makers leading to the Kyoto Protocol. Contributors to this volume include established experts from international organizations, nongovernmental organizations, and academia, including RaUl Estrada-Oyuela, who chaired the negotiating committee of the Framework Convention on Climate Change and the 1997 Kyoto meetings.